2010
DOI: 10.5194/tc-4-115-2010
|View full text |Cite
|
Sign up to set email alerts
|

Role of glaciers in watershed hydrology: a preliminary study of a "Himalayan catchment"

Abstract: Abstract. A large number of Himalayan glacier catchments are under the influence of humid climate with snowfall in winter (November–April) and south-west monsoon in summer (June–September) dominating the regional hydrology. Such catchments are defined as "Himalayan catchment", where the glacier meltwater contributes to the river flow during the period of annual high flows produced by the monsoon. The winter snow dominated Alpine catchments of the Kashmir and Karakoram region and cold-arid regions of the Ladakh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
117
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(119 citation statements)
references
References 46 publications
2
117
0
Order By: Relevance
“…Gangotri and other glaciers in this region are mostly fed by the summer monsoon and partly by winter snow. Western disturbances cause heavy snowfall from December to March over this region (Thayyen and Gergan 2010). Generally, seasonal melting starts in the month of May and continues till October (Dobhal, Gergan, and Thayyen 2008).…”
Section: Study Areamentioning
confidence: 99%
“…Gangotri and other glaciers in this region are mostly fed by the summer monsoon and partly by winter snow. Western disturbances cause heavy snowfall from December to March over this region (Thayyen and Gergan 2010). Generally, seasonal melting starts in the month of May and continues till October (Dobhal, Gergan, and Thayyen 2008).…”
Section: Study Areamentioning
confidence: 99%
“…Total discharge at any basin outlet is the sum of rain runoff, snow melt, glacier melt and base flow (Lutz and others, 2014). A variety of methods with different complexity such as empirical relationships between precipitation and discharge (Thayyen and Gergan, 2010), ice ablation models (Racoviteanu and others, 2013), the hydrograph separation method Khan, 2014a, 2015), chemical tracer methods (Racoviteanu and others, 2013) and distributed glacio-hydrological models (Lutz and others, 2014;Ragettli and others, 2015) are used to understand the discharge composition in the HK. Generally, the meteorological stations are installed at valley bottoms; knowledge of the precipitation distribution at glacier altitudes is nearly lacking, which makes it difficult to develop hydrological models.…”
Section: Hydrological Regimes Of Hk Riversmentioning
confidence: 99%
“…Solid precipitation collected in the standard rain gauges were measured as water equivalent after melting as per the India Meteorological Department (IMD) standard procedure. Further, standing snow depth and density were monitored 10 four times during the December-April period at different altitudes along the valley bottom from Gujjar Hut to the Basecamp and accumulated snow water equivalent was calculated (Thayyen and Gergan, 2010). Many of these surveys conducted immediately after the snowfall events have shown that the precipitation measured by the rain gauge underestimate it by 26-32%.…”
Section: Methodsmentioning
confidence: 99%
“…Himalayan system with dominant ISM, (2) Alpine system with dominant IWM and (3) Cold-arid system characterised by the absence of ISM in summer and subdued influence of IWM in winter (Thayyen and Gergan, 2010). In this paper we analyse the role of orography-moisture interplay in controlling the temperature distribution along the Himalayan slopes and high elevation cryospheric regions under monsoon regime and propose a modeling solution for estimating the SELR.…”
mentioning
confidence: 99%
See 1 more Smart Citation